METHOD TO DETERMINE UNSUITABLE DAYS FOR AGRICULTURAL SPRAYING (Nucleus, 2017)
Nowadays, the erratic weather makes it difficult to apply agrochemicals through the spraying procedure. The irregular agro-climatic conditions prevent or restrict the application through mechanized spraying, since they negatively affect factors such as the quality of the application, the operational and economic performance, and the agricultural planning and management. The aim of the current study is to validate a methodology able to accuracy the useful days unsuitable for agricultural spraying. The methodology is valid, because, despite the existing different agro-climatic conditions, it precisely defines the unsuitable useful days for spraying.